HUBUNGAN ANTARA KONFLIK PERAN GANDA DENGAN KOMITMEN KERJA PADA KARYAWATI UPT DIKLAT PEGAWAI PROVINSI RIAU - Sugiarto, Sugiarto (Jurnal Pendidikan Guru, 2018)
This study aims to determine whether there is a relationship between dual role conflict to work commitment on employee UPT Riau Province Employees Training. The hypothesis proposed in this research is there is a relationship of dual role conflict with work commitment on the employee UPT Diklat Pegawai Riau Province. This study took a sample of women who work and have children and husbands with status has become a permanent employee with the number of subjects as many as 30 participants. The scale used in this research is the scale of dual conflict and the scale of work commitment. Data analysis technique used is product moment analysis. Based on product moment correlation analysis test it can be seen that the results of this study did not indicate a significant relationship between variael dual role conflict and work commitment on employee UPT Diklat Pegawai Riau Province. The correlation coefficient is (r) -0.014 with p = 0.894 (p> 0.05).